Marriage behavior response to prime-age adult mortality: Evidence from Malawi - Yamauchi, Futoshi; Ueyama, Mika (International Food Policy Research Institute, 2008)
A drastic increase in AIDS-related mortality of the prime-age adult population can change many aspects of household and individual behavior. The death of prime-age adults decreases household income and, thus, decreases investment in human capital for the next generation. For individuals, high prime-age adult mortality influences people’s perceptions on potential risks in family formation such as finding a marriage partner. For example, in a society where the AIDS epidemic is prevalent, a possible behavioral change in the marriage market in response to an increase in prime-age adult mortality is to marry earlier to avoid their exposure to HIV. Since the marriage decision is key to the way a family is structured, current AIDS mortality risks can potentially have long-term impacts propagating to the next generation.